Processo antissolvente supercrítico para obtenção de dispersões sólidas - Yoshida, Valquíria Miwa Hanai [UNESP] (2014)
In this study we proposed the use of supercritical antisolvent process (SAS), in which carbon dioxide was selected as antisolvent agent, to obtain drug controlled release system. Factorial 32 experimental design use the of zidovudine and poly (L-lactic acid) ratio (AZT:PLLA ) as X1 factor, also the temperature and pressure conditions as X2 factor, both independent variables, the process yield and particles macroscopic morphology represented the dependent variables. In this study, the dependent variables determined the product that have been selected to solid state characterization, AZT content, type, release kinetics, and intestinal permeation. Solid state characterization used X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), infrared spectroscopy with Fourier transform (FTIR), and differential scanning calorimetry (DSC). The AZT content was determined by validated analytical methodology. The dissolution test provided data for AZT release and release kinetics evaluation. The rat everted gut sac model was take on for the ex vivo study of intestinal permeation of AZT. The L3 (91.54 % yield and sample with uniform appearance), L5 and L9 lots (59.06 % and 51.50 % yield , respectively , both of which resulted in samples with non-uniform and solid filamentous appearance) resulting from factorial 32 planning were selected for analytical studies. The L3batch ratio of AZT:PLLA (1:2, w/w) resulted in a high yield of 91.54 % and 58.76 % AZT content compared to batches produced, and was selected for the study of intestinal permeation . The AZT permeability from L3 lot (9.87 ± 0.47%) was higher than pure AZT (3.84 ± 0.45 %). AZT remained in crystalline form and PLLA remained in semi - crystalline form, in lots L3, L5, and L9 produced by the SAS process, when evaluated by SEM, XRD, DSC, and FTIR. This study demonstrated that it is possible to use the SAS process to obtaining modified release systems for poorly permeable drugs ...